The Effect of Tax Aggressiveness on Corporate Social Responsibility Disclosures (Study on Listed Companies on the Indonesia Stock Exchange) - Ferdyan Saputra; Niken Ayuningrum; Dedi Handoko; Tanto Tanto (Politeknik Negeri Madiun, 2023)
Many companies consider tax costs to be the part of lost corporate profits, so companies go through various ways to maximize profits by reducing tax costs. One of the ways that companies do this is by taking aggressive tax measures. The purpose of this study was to show the effect of tax aggressiveness on corporate social responsibility disclosure. The study was conducted on 89 companies listed on the Indonesia Stock Exchange between 2015 until 2021 using the OLS regression analysis model and sensitivity analysis tests. The results showed that tax aggressiveness no effect the disclosure of corporate social responsibility, although this effect is only seen in the next one year's observation (t+1). These results show that the effect of a policy cannot be measured directly within the same time frame as when it was created. The study also found that only company size had any effect on social responsibility disclosure, while leverage, capital intensity and profitability had no effect on social responsibility disclosure.